Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/20543581211029389
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes Following Kidney-Pancreas Transplantation in Alberta, Canada: Research Letter

Abstract: Background: Simultaneous kidney-pancreas transplantation (SPK) has benefits for patients with kidney failure and type I diabetes mellitus, but is associated with greater perioperative risk compared with kidney-alone transplantation. Postoperative care settings for SPK recipients vary across Canada and may have implications for patient outcomes and hospital resource use. Objective: To compare outcomes following SPK transplantation between patients receiving postoperative care in the intensive care unit (ICU) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…9 Recently, a 17-year Canadian study also reported the lack of difference in hospital stay and adverse outcomes between patients being cared for in critical care and ward environments following simultaneous pancreas and kidney transplants. 10 Patients in the enhanced perioperative care wards will be looked after by their transplant team and the multidisciplinary teams led by consultants that are specialized in anesthesia, perioperative, and intensive care medicine. The close working relationship between clinical staff that work in the enhanced care and critical care areas would ensure patients receive the same standard of physiological monitoring after their transplants and timely escalation to intensive care should the need for higher-level monitoring or organ support arise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, a 17-year Canadian study also reported the lack of difference in hospital stay and adverse outcomes between patients being cared for in critical care and ward environments following simultaneous pancreas and kidney transplants. 10 Patients in the enhanced perioperative care wards will be looked after by their transplant team and the multidisciplinary teams led by consultants that are specialized in anesthesia, perioperative, and intensive care medicine. The close working relationship between clinical staff that work in the enhanced care and critical care areas would ensure patients receive the same standard of physiological monitoring after their transplants and timely escalation to intensive care should the need for higher-level monitoring or organ support arise.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recently, a 17-year Canadian study also reported the lack of difference in hospital stay and adverse outcomes between patients being cared for in critical care and ward environments following simultaneous pancreas and kidney transplants. 10…”
Section: Discussionmentioning
confidence: 99%